Deep Tissue Sculpture in Neck Rejuvenation: Review of 641 Consecutive Cases - Samir M. Ghoraba, MD, MRCS (Plastic and Reconstructive Surgery, Global Open)
Background:. Enhancing neck contour is a primary goal for individuals seeking facial and neck rejuvenation. However, the literature on deep neck sculpture and its potential complications is scarce. Methods:. The records of 641 patients with deep plane neck lift and deep tissue sculpture were reviewed retrospectively between 2014 and 2023. The surgical techniques used by the author were addressed comprehensively and supplemented with videos. The outcomes and complications were reported. Results:. A total of 1861 consecutive patients underwent deep plane facelift. Of these, 641 patients (34.4%) underwent deep neck surgery, with an average age of 52 years; 14.6% were men, and 29% were smokers. A total of 12.3% experienced complications after deep neck sculpture. The most common complications were subcutaneous serous collection (4.3%), followed by marginal mandibular neuropraxia (3.3%) and hematomas (2.96%). Parotid sialocele was the least frequent complication among enrolled patients (0.3%). Conclusions:. Deep neck sculpture presents an effective and safe technique for patients seeking neck rejuvenation.